Mengefektifitaskan Minat Belajar Siswa Dengan Strategi Pembelajaran Future Planning (Pengembangan Konseling Yang Berorientasi Pada Perencanaan Masa Depan) Pada Bidang Bimbingan Sosial Siswa di SMA Negeri 1 Babadan, Ponorogo - Triyono Triyono (Universitas Mathla'ul Anwar Banten, 2020)
In this action research, it shows that the Future Planning approach (Development of Counseling Oriented to Future Planning) in teaching and learning activities in the field of social guidance Information Service Material for Adolescent Psychology for Class XI-MIPA-2 Odd Semester students at SMA Negeri 1 Babadan, Ponorogo Regency shows that each student has various needs which include physical, spiritual and social needs that support achievement in learning. This is shown from the results of observations of researchers in a series of action research activities, especially teaching and learning activities in class. The results obtained include activities, motivation and learning achievement. For learning achievement is shown in the evaluation results in cycle 3 obtained by 36 students with the category of less value is 0.01 - 0.00 with a frequency of 0 and a percentage of 0.00% (NIHIL), the medium value category is 6.01 - 8.00 with a frequency 18 and the percentage is 56.25%, while the category of good learning outcomes is 8.01 - 10.00 with a frequency of 14 the percentage is 43.75%. So that in this research activity it is stated Completely.